A hybrid silicon evanescent laser with sampled Bragg grating structure based on the reconstruction equivalent chirp technique for silicon photonics. (28th April 2021) - Meng, Ranzhe; Wang, Hailing; Shi, Tao; Wang, Mingjin; Zheng, Wanhua
Abstract: In this paper, we report on a direct bonding hybrid silicon evanescent laser with sampled Bragg grating structure based on the reconstruction equivalent chirp (REC) technique for the first time. By the design of the REC technique, the hybrid silicon evanescent laser in the +1st order channel is emitted. The optical mode is evanescently coupled between the III and V waveguide and silicon waveguide. A laser with 24 mA threshold current and 0.3 mW output power from silicon waveguide at 50 mA under the continuous wave operation is obtained.